2020
DOI: 10.1021/acschembio.9b01023
|View full text |Cite
|
Sign up to set email alerts
|

Förster Resonance Energy Transfer Based Biosensor for Targeting the hNTH1–YB1 Interface as a Potential Anticancer Drug Target

Abstract: The Y-box binding protein 1 (YB1) is an established metastatic marker: high expression and nuclear localization of YB1 correlate with tumor aggressiveness, drug resistance and poor patient survival in various tumors. In the nucleus, YB1 interacts with and regulates the activities of several nuclear proteins, including the DNA glycosylase, human Endonuclease III (hNTH1). In the present study, we used Förster Resonance Energy Transfer (FRET) and AlphaLISA technologies to further characterize this interaction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 47 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…In addition, YB-1 binds to the DNA repair proteins MSH2, DNA polymerase δ, Ku80, and WRN75. A recent study demonstrated that human endonuclease III (hNTH1) is a DNA repair protein and bifunctional DNA glycosylase that binds to YB-1 in the nucleus, and the hNTH1-YB-1 interface plays a role in the response to cisplatin in MCF7 cells [ 71 ]. YB-1 can be PARylated (Poly(ADP-ribosylation)) by PARP1 during the process of interacting with damaged DNA [ 72 ].…”
Section: The Functions and Mechanisms Of Yb-1mentioning
confidence: 99%
“…In addition, YB-1 binds to the DNA repair proteins MSH2, DNA polymerase δ, Ku80, and WRN75. A recent study demonstrated that human endonuclease III (hNTH1) is a DNA repair protein and bifunctional DNA glycosylase that binds to YB-1 in the nucleus, and the hNTH1-YB-1 interface plays a role in the response to cisplatin in MCF7 cells [ 71 ]. YB-1 can be PARylated (Poly(ADP-ribosylation)) by PARP1 during the process of interacting with damaged DNA [ 72 ].…”
Section: The Functions and Mechanisms Of Yb-1mentioning
confidence: 99%
“…A direct interaction between NTH1 and the multifunctional YB1 protein has indeed been reported to occur in tumor cells in response to genotoxic stress. Through this interaction, YB1 has been shown to stimulate the AP-lyase activity of NTH1 [106,162]. Several reports have demonstrated that the level of nuclear expression of YB1 is predictive of drug resistance and poor prognosis [163][164][165][166][167][168] and the increased abundance of the NTH1-YB1 complex in tumor cells after exposure to genotoxic stress, including cisplatin treatment, could explain the increased resistance of these cells to anticancer agents [169,170].…”
Section: Regulation Of Dna Glycosylasesmentioning
confidence: 99%
“…shed light on the mode of inhibition of these promising molecules and the molecular contacts underlying this unexpected specificity. [193] (A), the DNA glycosylase activity [197] (B) of DNA glycosylases, or of the interaction interface (C) between a DNA glycosylase (here, NTH1) and its cellular partner (YB1) [162]. FRET: Förster resonance energy transfer.…”
Section: Finding Inhibitors Of Dna Glycosylasesmentioning
confidence: 99%
See 2 more Smart Citations